2013
DOI: 10.1002/chem.201202719
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Photoactivity of TiO2(B)/Anatase Core–Shell Nanofibers by Selectively Doping Cerium Ions into the TiO2(B) Core

Abstract: Cerium ions (Ce(3+)) can be selectively doped into the TiO2(B) core of TiO2(B)/anatase core-shell nanofibers by means of a simple one-pot hydrothermal treatment of a starting material of hydrogen trititanate (H2Ti3O7) nanofibers. These Ce(3+) ions (≈0.202 nm) are located on the (110) lattice planes of the TiO2(B) core in tunnels (width≈0.297 nm). The introduction of Ce(3+) ions reduces the defects of the TiO2(B) core by inhibiting the faster growth of (110) lattice planes. More importantly, the redox potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 42 publications
3
40
0
1
Order By: Relevance
“…These diffraction patterns reveal that both mixed-phase anatase and TiO 2 (B) are not in a balanced volume ratio, as T(B) is always the precursor and has partially converted into anatase. In our previous study [13][14][15], we found that the aggregation of anatase and TiO 2 (B) phases in T(AB)_T and T(AB)_H samples are not random, but rather the materials are annealed together with a well-matched phase interface. The phase interface allows photogenerated electrons and holes to readily migrate across the interfaces, which can reduce the recombination of the photogenerated charges and thus improve the photoactivity in reactions [13,14].…”
Section: Structural Characterization Of the Tio 2 Nanofibersmentioning
confidence: 97%
See 3 more Smart Citations
“…These diffraction patterns reveal that both mixed-phase anatase and TiO 2 (B) are not in a balanced volume ratio, as T(B) is always the precursor and has partially converted into anatase. In our previous study [13][14][15], we found that the aggregation of anatase and TiO 2 (B) phases in T(AB)_T and T(AB)_H samples are not random, but rather the materials are annealed together with a well-matched phase interface. The phase interface allows photogenerated electrons and holes to readily migrate across the interfaces, which can reduce the recombination of the photogenerated charges and thus improve the photoactivity in reactions [13,14].…”
Section: Structural Characterization Of the Tio 2 Nanofibersmentioning
confidence: 97%
“…The bandgaps of anatase and TiO 2 (B) phase obtained are ~3.19 and ~3.05 eV, respectively. In our previous study, the conduction band (CB) and valence band (VB) edge potentials of TiO 2 (B) nanofibers were located at -0.33 and 2.72 eV [15]. The corresponding edge potentials of anatase nanofibers were located at -0.38 and 2.80 eV, respectively.…”
Section: Charge Transfer In the Mixed Phase Tio 2 Nanofibersmentioning
confidence: 99%
See 2 more Smart Citations
“…Cerium ions were easily and selectively doped into the TiO 2 (B) (110) plane in fiber-shaped TiO 2 (B)/anatase core-shell nanostructures in order to enhance the photoactivity. [7] Additionally, the (010) plane is a stable plane that exhibits the largest area in TiO 2 (B) structure, shows favorable bidentate adsorption of ethylene glycol, and plays an important role in nanosheet-shaped TiO 2 (B). [8] Clearly, the two planesplay key roles in various applications of nanoscale TiO 2 (B).…”
mentioning
confidence: 99%